2020
DOI: 10.1111/jocn.15141
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with spiritual care competencies in Taiwan’s clinical nurses: A descriptive correlational study

Abstract: Aims and objectives:To determine factors associated with nurses' spiritual care competencies.Background: Holistic nursing care includes biopsychosocial and spiritual care.However, nurses are limited by a lack of knowledge, time constraints and apprehension of assessing spiritual issues, which leaves them unable to assess and meet patients' spiritual needs. Thus, when patients experience spiritual distress, clinical nurses lose the opportunity to support spiritual growth and self-actualisation. In Taiwan, spiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 35 publications
8
17
0
1
Order By: Relevance
“…Lastly, we did not separate perspectives of physicians from nurses during content analysis but treated them as a whole. Despite more extensive literature on initiatives in spiritual competency for nurses than physicians in Taiwan, the ramifications of these training differences for physician and nurse perspectives on spiritual care did not stand out in the present study and this represents another potential limitation [8,11,13,26]. More research on processes of education and training in spiritual care in Taiwan is needed, especially for physicians, to elucidate any key differences between physicians and nurses in spiritual care practice.…”
Section: Study Limitationsmentioning
confidence: 69%
See 1 more Smart Citation
“…Lastly, we did not separate perspectives of physicians from nurses during content analysis but treated them as a whole. Despite more extensive literature on initiatives in spiritual competency for nurses than physicians in Taiwan, the ramifications of these training differences for physician and nurse perspectives on spiritual care did not stand out in the present study and this represents another potential limitation [8,11,13,26]. More research on processes of education and training in spiritual care in Taiwan is needed, especially for physicians, to elucidate any key differences between physicians and nurses in spiritual care practice.…”
Section: Study Limitationsmentioning
confidence: 69%
“…Hospice and palliative care physicians in the National Taiwan University Hospital are primarily family medicine physicians, who receive mandatory hospice training in Taiwan; spiritual care, including learning the role of CBC's, is a mandatory topic in their training curriculum [12]. For nurses working in hospice, more initiatives in spiritual care training and research have been undertaken across Taiwanese institutions [8,13]. As all palliative physicians and nurses in Taiwanese healthcare are also hospice staff, hospice and palliative will be used interchangeably to refer to our physician and nurse populations [12].…”
Section: Spiritual Care In Taiwanmentioning
confidence: 99%
“…In this study, Chinese nurses experienced mild‐to‐moderate levels of spiritual care competencies. Compared with the mean scores for spiritual care competencies of nurses from Malta (Attard et al., 2014), Iran (Ebrahimi et al., 2016) and Taiwan (Hsieh et al., 2020) where the scores were 105.73, 95.20 and 84.67, the total score for spiritual care competencies was 60.88, which was significantly lower ( p <.001). These findings reveal that nurses from China are less able to provide spiritual care.…”
Section: Discussionmentioning
confidence: 89%
“…Ebrahimi et al., (2017) investigated the spiritual well‐being and competencies of 555 Iranian nurses and found that nurses experienced moderate levels of spiritual care competencies. Hsieh et al., (2020) surveyed 294 nurses from Taiwan and found moderate levels of spiritual care competencies. Even though studies from different countries present similar results for spiritual care competencies of nurses, some limitations should be considered, such as sample size, differences in economic development and diversity of culture and nation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of spiritual care, nurses have expressed a need to learn how to provide spiritual care. Integrating spiritual care into nursing curricula could meet that need during the nurse formation process [12]. Previous studies have reported related demographic and characteristics factor such as a nurse's gender, religion, experience, carrier, and education level to individual perceptions of spirituality and spiritual care [13]- [15].…”
Section: Introductionmentioning
confidence: 99%